Latent profile analysis of five childhood maltreatment subtypes and its associations with smartphone addiction among Chinese adolescents - Chang Peng; Nan Zhang; Junhan Cheng; Fajuan Rong; Jie Hu; Zixuan Xu; Meiqi Guan; Yizhen Yu (Scientific Reports)
Abstract Most victims of childhood maltreatment have experienced more than one form. Yet, few studies have investigated co-occurrence of multiple childhood maltreatment subtypes (including physical abuse, emotional abuse, sexual abuse, physical neglect, and emotional neglect) using person-centered approaches in Chinese adolescents. Moreover, little is known about associations between different childhood maltreatment subtypes and smartphone addiction. This study aims to examine the specific effects of different childhood maltreatment patterns on smartphone addiction and the potential gender and residence differences. A multistage cluster sampling was adopted for Chinese adolescents aged 12 to 18 years across five representative provinces. The Childhood Trauma Questionnaire-Short Form was used to measure childhood maltreatment subtypes and Mobile phone Addiction Index was used to assess smartphone addiction. Childhood maltreatment patterns were analyzed via latent profile analysis (LPA) in Mplus. Of 23,478 Chinese adolescents, LPA yielded four distinct childhood maltreatment profiles: Low Maltreatment (Profile 1, 86.7%), High Emotional Maltreatment and Low Sexual Abuse (Profile 2, 9.2%), Moderate Multiple Maltreatment (Profile 3, 3.5%), and High Sexual Abuse with Multiple Maltreatment (Profile 4, 0.6%). Logistic regression analysis showed that members of Profile 2, 3, and 4 had higher odds ratio of smartphone addiction than members of Profile 1 (p < .01). Subgroup analysis indicated that members of Profile 4 had a higher odds ratio of smartphone addiction only for boys and rural adolescents (p < .01).. Childhood maltreatment subtypes rarely occur in isolation, and exposure to multiple childhood maltreatment subtypes will increase the risk of smartphone addiction. Particularly, boys and rural adolescents may deserve more attention in preventive strategy.